A LITERARY ANALYSIS ON FIGURE OF SPEECH IN KAKAWIN NITISASTRA - Manuaba, Ida Bagus Arya Lawa; Sudirman, I Nyoman (Yavana Bhasha : Journal of English Language Education, 2018)
Kakawin Nitisastra, one of ancient Javanese scriptures, holds a lot of figurativewritings in it. Revelation and analysis of those figurative language are important to enrichIndonesian literary culture and introduce it to character education in present days. The aimsof this study are (1) to identify types of figure of speech used in Kakawin Nitisastra, (2) toidentify functions of those figurative speech, and (3) to reveal the meanings behind them. Byapplying literature-based qualitative method, the result of this study reveals that KakawinNitisastra contains mostly similes, symbolism, allegory, hyperboles, and personificationsrelated to animals, plants and ancient beliefs in the Vedas. The figures of speech have at leastfour functions namely to give examples, to compare qualities, to criticize, and to remindreaders about proper deeds in the society.